Problematika Kekerasan dalam Rumah Tangga Penyebab Runtuhnya Tatanan dan Tujuan Perkawinan: Studi Analis Tentang Dekadensi Moral Kaula Muda - Suaidi Suaidi (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Marriage is a sacred goal in establishing a happy home that is eternal and based on the Almighty Godhead. The sacred bond of marriage is part of God's command, in order to fulfill basic, private needs. In fact, marriage is lived with full happiness, mutual love and meaning of life between husband and wife who were previously not the same, both in educational, family and cultural backgrounds. An ideal marriage is where a husband and wife unite their differences in unity of strength to form a happy household. In reality, not all married couples are able to realize happiness together in arranging their family's future life. Disagreements between husband and wife are triggered by differences in understanding in creating domestic happiness. Differences that were originally normal often lead to domestic violence. Married couples who are unable to control their emotions sometimes commit violence, whether by the wife or the husband, but in general domestic violence is carried out by the husband against his wife. This research tries to provide an overview of the triggers for domestic violence and solutions to overcome it.